Aluminum for Near Infrared Plasmonics: Amplified Up‐Conversion Photoluminescence from Core–Shell Nanoparticles on Periodic Lattices. Issue 1 (9th November 2020) - Gao, Yuan; Murai, Shunsuke; Shinozaki, Kenji; Ishii, Satoshi; Tanaka, Katsuhisa
Abstract: Aluminum (Al) is known as a plasmonic material effective in a wide frequency range up to the ultraviolet, while its plasmonic properties in the near infrared region have been less explored. In this study, up‐conversion (UC) photoluminescence is amplified by using an Al nanostructure to demonstrate that Al is a useful plasmonic material in the near infrared region as well. A periodic lattice of Al nanocylinders is selected as a plasmonic nanostructure, where the size of nanocylinder and the period of the lattice are tuned to match both the localized surface plasmon resonance and in‐plane diffraction to the absorption wavelength (λ = 980 nm) for the UC process. Core–shell‐type UC nanoparticles (NPs) are designed to suppress the energy transfer from NPs to Al cylinders which reduces the UC photoluminescence intensity. The resulting optimized core–shell UCNPs combined with the Al plasmonic lattice leads to over 100‐fold enhancement of UC intensity. The use of Al instead of conventional Au as a plasmonic material is beneficial from the point of view of low cost and abundance of element. Abstract : Over 100‐fold up‐conversion (UC) luminescence enhancement is shown from the core–shell UC nanoparticles on a 2D Al nanocylinder array resonating at 980 nm light. This study proves that Al is a practical plasmonic material in the near infrared region and paves a way to modulate the UC for many applications.